Nordic Perspectives on the Discourse of Things Sakprosa Texts Helping Us Navigate and Understand an Ever-changing Reality - Nyström Höög, Catharina; Rahm, Henrik; Thomassen Hammerstad, Gøril (Springer Nature, 2023)
This open access book deals with the role of written texts in an increasingly diverse and dynamic society, bringing together a series of studies anchored in the Scandinavian research tradition of sakprosa, which roughly translates as 'subject-oriented prose' or 'professional communication'. The authors examine the written text's capacity to transcend contextual boundaries, as a crucial factor in the importance of capturing and maintaining content as a manageable entity. The chapters each deal with a text type that manages complex content in a specialized way, including genre shifting in CSR reports, discourse networks in modern digital culture, digital and social media crisis communication, and epistemic positions in non-fiction. This book is relevant to fields such as text research, professional/digital communication, discourse analysis and literacy studies, and may also be of interest to disciplines such as history, rhetoric, organization studies, media studies/journalism, and linguistics.